Análisis e interpretación a los estados financieros de la distribuidora M & S Franquiciado Disensa, período 2010, 2011,2012 - Guerrero Saavedra, Erika Gabriela (2014)
This research entitled, ANALYSIS AND INTERPRETATION OF FINANCIAL STATEMENTS OF THE DISTRIBUTOR M & S FRANCHISEE DISENSA, YEAR 2010, 2011,2012 are made in the fulfillment of a prerequisite to qualify for the title of Engineer in CPA Accounting and Auditing in The National University of Loja. Compliance was given to the goals outlined in the approved project by collecting the financial statements in order to perform the analysis and interpretation of data, both horizontal and vertical analysis, in order to compare the results obtained in the three years of study; financial ratios applied helped them check the status of the company, and finally the analysis report according to the results of the indicators was made. When this work is concluded that through the analysis and interpretation of financial statements can be verified that the company has sufficient assets amount to meet the needs according to their main activity that is dedicated, is hereby reason managers financial analysis is recommended periodically in order to make appropriate decisions.